(untitled) (Annals of Medical Research, 2021)
Aim: The proportion of an individual’s index finger to their ring finger, their 2D/4D proportion, is influenced by prenatal sex hormones and is known to be higher in women. It has been related to certain psychological, behavioral and physiological characteristics. Therefore, we aimed to discover whether 2D/4D proportion is related to preoperative anxiety. Materials and Methods: We included 108 ASA I or II patients with an age range of 18 to 65 years who were to undergo elective surgery. The APAIS-A and APAIS-B tests were used to determine the patients’ anxiety levels and their desire to obtain information regarding the preoperation. Digit lengths were quantified via a digital caliper with 0.01 mm sensitivity. 2D/4D proportions were measured bilaterally, allowing us to determine the differences between the fingers of both hands. Patients were grouped according to their 2D/4D proportions as ≥1 mm and <1 mm. Results: We found no statistical relation in 2D/4D proportions of either hand (p=0.190 for right and p=0.677 for left).Also, neither right-hand nor left-hand proportions were statistically associated with APAIS scores (p=0.155 and p=0.533, respectively). In terms of differences in length, neither hand revealed any correlation to APAIS scores (right-hand: p=0.821 for <1 mm and p=0.233 for ≥1 mm; left-hand: p=0.388 for <1 mm and p=0.604 for ≥1 mm). Conclusion: Although simple and easy anthropometric measurements, 2D/4D proportions and 2D-4D sizes were found to be unrelated to preoperative anxiety. Our results can be of aid to future multicentered research with larger and more homogenized patient samples.